Pakaian Ideal Seorang Muslimah (Studi Komparatif dalam Pentafsiran Surah Al-A’raf ayat 26 antara Kitab Tafsir Al-Maraghi dan Tafsir Al-Azhar): Al-Maraghi dan Buya Hamka - Ana Maftuhatul Khasanah; Fattah, Mohammad Fattah (Advances in Humanities and Contemporary Studies, 2021)
ABSTRACTClothing becomes one of the needs of human nature to interact with each other in society. Muslimah clothing can be defined as clothing for Muslim women and its function is to cover the genitals as prescribed by the teachings of the Religion, and the goodness of women themselves. Clothing also serves as jewelry, as Allah SWT says in the Qur’an Surah al-A’raf verse 31. There are two types of clothing, namely clothing that is worn as an obligation and clothing that is only worn as decoration. Here the author will describe the ideal clothing by the concept of syari’ah, especially through the verses of the Qur’an surah al-A’raf verse 26 perspective of two commentators Syeikh Ahmad Musthafa al-Maraghi and Buya Hamka. The type of research used library research. It is collecting data or compiling materials (literature review) that have to do with the problems being researched. The primary data used comes from the book tafsir al-Maraghi by Syeikh Ahmad Musthafa al-Maraghi and the book tafsir al-Azhar by Haji Abdul Malik Karim Amrullah or commonly referred to as Buya HAMKA. While the secondary data comes from the relevant books in this study. The results of the research put forward the ideal Concept according to them. Keywords: Clothing (Libas),Ideal,Muslimah,Contemporary